2021
DOI: 10.1038/s41558-021-01059-w
|View full text |Cite
|
Sign up to set email alerts
|

Tradeoff of CO2 and CH4 emissions from global peatlands under water-table drawdown

Abstract: Water table drawdown across peatlands increases carbon dioxide (CO 2 ) and reduces methane (CH 4 ) emissions. The net climatic effect remains unclear. Based on observations from 130 sites around the globe, we found a positive (warming) net climate effect of water table drawdown.Using a machine-learning based upscaling approach, we predict that peatland water table drawdown driven by climate drying and human activities will increase CO 2 emissions by 1.13 (95% interval: 0.88 -1.50 ) Gt yr -1 and reduce CH 4 by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
84
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(90 citation statements)
references
References 38 publications
5
84
0
1
Order By: Relevance
“…They suggest in fact, that lowering of the water table will increase CO 2 emission rates from peatlands and might further compromise their carbon balance. All this is coherent with the enhancement in GHG emissions, only partly offset by inhibition of methanogenesis, that was recently predicted through a machine learning upscaling approach by Huang et al [23].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…They suggest in fact, that lowering of the water table will increase CO 2 emission rates from peatlands and might further compromise their carbon balance. All this is coherent with the enhancement in GHG emissions, only partly offset by inhibition of methanogenesis, that was recently predicted through a machine learning upscaling approach by Huang et al [23].…”
Section: Discussionsupporting
confidence: 82%
“…The greater incidence and length of drought periods fostered by climate change will cause a more and more frequent onset of aerobic conditions in thicker sections of peat deposit profiles [21,22]. Impacts of water table lowering on GHG emissions from peatlands are highly variable: most studies report reductions in CH 4 emissions, although the overall balance foresees a net increase from 0.73 to 0.86 Gt CO 2 -eq yr −1 by the end of the century [23]. The factors that affect the mechanisms underlying this variability have not been fully elucidated yet, but HA certainly play a pivotal role [19].…”
Section: Introductionmentioning
confidence: 99%
“…Carbon dioxide, methane, and nitrous oxide can be significant contributors to greenhouse gas emissions from wetlands (5) especially from disturbances that liberate previously stabilized carbon e.g. (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…These shifts may provide optimal conditions for CH4 production and emissions, particularly in the initial decades following thaw. Peatland CH4 emissions are constrained by the water table position (Huang et al, 2021;Strack et al, 2004), and surface inundation leads to increased CH4 emissions (Tuittila et al, 2000). Methane production and emissions are positively influenced by soil temperatures (Hopple et al, 2020;Olefeldt et al, 2017), and peatland CH4 emissions have been shown to increase when both the water table position and temperatures are high (Grant, 2015).…”
Section: Introductionmentioning
confidence: 99%